Pengembangan Koperasi Simpan Pinjam Berbasis Teknologi Informasi pada Koperasi Simpan Pinjam Jaya Makmur - Nurjayadi Nurjayadi; Herwin Herwin; Khusaeri Andesa; Torkis Nasution (LPPM UMRI, 2020)
The Savings and Loans Cooperative is under the management of BUMDes Jaya Makmur and is engaged in a productive economy. The problems are the Ability of Financial Bookkeeping, Financial Governance, Low Public Interest. The field of financial accounting, namely how to improve the ability of employees to do financial bookkeeping. The solution taken is a common understanding of the need for a bookkeeping system in KSP management, providing financial system training for employees, providing assistance. The field of financial governance, namely how to implement information technology to implement financial governance. The solution is to install financial applications, provide training on the use of KSP financial applications, implement financial applications, assist in the use of applications. Areas of increasing public interest, namely How to increase public interest in borrowing and saving money to BUMDes Savings and Loans, the solution given is a common understanding of the use of technology, implementation of a transparent financial system, assistance in implementing the membership system. The use of information technology in the management of KSP increases productivity and efficiency of performance and governance, increases member satisfaction, increases transparency, and better management accountability.